Investigations on Nine Flocks Infected with Infectious Bursal Disease Virus (IBDV) in Khartoum State (Sudan) - Babiker, M.A.A.; Yahia, I.E.; Nora, K.; Tawfeeg, E.M. (International Journal of Poultry Science, 2008)
Nine flocks suspected to be infected with IBD between January to December 2005 were followed up in Khartoum state during the period of the clinical disease course. Our careful investigations showed that the disease occurred in different poultry producing areas all around the year and causing mortality between 9 - 49%. All cases of IBD reported to the governmental veterinary hospitals during this period were occurred in light egg type leghorn and no heavy meat broiler chickens was reported during the period of the survey. The four anti-IBDV vaccine strains commercially available in Sudan market (D78, Bio-Gumboro, Gumboro3) including hot vaccine (228E) and a variety of vaccination schedules performed failed to protect the surveyed flocks from clinical IBD infection. Diagnosis based on clinical signs and postmortem gross lesions was confirmed in all surveyed flocks by serological tests (ELISA), in seven out of nine flocks by histopathological examination and by isolation methods in six out of nine flocks.